Autologous fascia lata transplantation for heart valve replacement: A two-year experience at the National Heart Hospital, London. Issue 1 (January 1972) - Dalichau, H.; Gonzalez-Lavin, L.; Ross, D. N.
Abstract : Between April 1969 and December 1970, 201 patients underwent 262 valve replacements with frame-mounted autologous fascia lata valves in the aortic, mitral, and/or tricuspid positions at the National Heart Hospital. A single fascia lata valve was inserted in 146 patients and multi-valve replacement was performed in 55 instances. Hospital and late mortality are comparable with that following other procedures of heart valve replacement. One hundred and fifty-four patients with 193 fascia lata valves were available for follow-up. A retrospective analysis of this method of valve replacement has been undertaken to assess the suitability of fascia lata as a heart valve substitute as well as the clinical results achieved by this method of valve replacement.